Pricing of options with stochastic volatilities: Application to agricultural commodity contracts - Nasibrola Lordkipanidze; William G. Tomek (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2014)
The empirical evidence in this paper supports the existence of seasonality, time-to-maturity, and long-memory effects in the volatility of prices, but not in the returns themselves, in corn and soybean futures markets. This volatility is modeled as an Orenstein-Ulenbeck process driven by fractional Brownian motion. The inclusion of long-memory stochastic volatility is found to have a significant impact upon the term structure of implied volatilities, and should be able to provide better estimates of in- and out-of-the money options prices.
Keywords: 330